Evaluating Mustard Meal as a Partial Replacement for Soybean Meal in Performance of Japanese Quail - Pandey, Utshav; Dhital, Bhargab; Neupane, Huma; Neupane, Narayan (Journal of the Institute of Agriculture and Animal Science, 2025)
This experiment evaluated the effects of partially replacing soybean meal (SM) with mustard meal (MM) at varying crude protein (CP) levels on the growth performance, egg production, and economic viability of Japanese quail. A 3 x 3 factorial experiment in a Completely Randomized Design employed nine dietary treatments were used. These comprised three CP levels (20%, 22%, and 24%) and three protein source combinations: SM only, 3% SM replaced by MM, and 5% SM replaced by MM. A total of 450 birds were distributed across five replicates per treatment. Over a 65-day period, data on feed intake, body weight gain, feed conversion ratio (FCR), age at first egg, egg number, and egg weight were collected and analyzed using ANOVA in R Studio, with benefit-cost (B:C) ratio calculated for economic assessment. Results indicated that dietary CP level significantly influenced performance, with 24% CP promoting the best weight gain and FCR during their growth. Protein source also had a significant effect; 3% MM inclusion (replacing SM) consistently resulted in higher weight gain and egg production compared to SM-only or 5% MM diets. The interaction was significant for key laying parameters: birds fed a 24% CP diet with 3% MM inclusion (CQ) exhibited the earliest sexual maturity (36.67 days), the highest egg production (22.33 eggs/bird), and the optimal B:C ratio (1.91). It is concluded that soybean meal can be partially replaced with 3% mustard meal in a 24% CP diet without compromising the growth performance. This formulation enhances egg production, improves feed efficiency, and maximizes economic returns, providing a cost-effective alternative for quail production in Nepal.